Intellectual Capital and Firm Performance: Value-Added Intellectual Coefficient - Ahmed, Znar Nahro; Hussin, Muhammad Rosni Amir (Journal of Accounting Research, Organization and Economics, 2023)
Objective This article is concerned with the influence of IC and understanding the vital success factor of the components on firm performance. This study aims to deliver a complete review of existing evidence related to the effect of IC on firm performance.Methodology A review of the literature was conducted based on the five components of intellectual capital: human capital, structural capital, capital employed, relational capital, and innovation capital. Using electronic searches in three databases (Emerald, Web of Science, and Scopus) and keywords to identify relevant studies, 48 published studies are identified from 2010-2020.Results The results indicated that research focusing on IC and its impact on company performance has gained growing interest within scholarly works over recent decades. Furthermore, a steadier rise in interest can be observed from 2017 onwards, reaching its peak in 2019 with a 50% acceleration in the publication rate compared to the preceding year. In addition, the widely accepted method is the value-added intellectual coefficient approach without any modification or extension. Moreover, out of reviewed (48) studies only (12) of them utilized an adjusted VAIC model.Novelty/Originality This paper contributes to IC literature by providing a unique review of the IC and firm performance field of research.